2016
DOI: 10.1039/c6ra18731e
|View full text |Cite
|
Sign up to set email alerts
|

3-Aminopropyltrimethoxysilane and graphene oxide/reduced graphene oxide-induced generation of gold nanoparticles and their nanocomposites: electrocatalytic and kinetic activity

Abstract: The role of graphene oxide (GO)/reduced graphene oxide (rGO) in the 3-aminopropyltrimethoxysilane-mediated synthesis of gold nanoparticles in the presence of formaldehyde is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 57 publications
2
22
0
Order By: Relevance
“…16 It is generally known that the catalytic performances of Au NCs depend strongly on their morphology, size, surface structure and crystallinity. [17][18][19][20] Therefore, the shape-controlled synthesis and relevant applications of Au NCs have been widely studied and obtained great success during the past decade. Many efforts have been devoted to the shape-controlled synthesis of Au NCs with different morphologies, such as nanospheres, nanorods, nanowires, nanodendrites, nanosheets, nanocombs and pentagon-shaped particles.…”
Section: Introductionmentioning
confidence: 99%
“…16 It is generally known that the catalytic performances of Au NCs depend strongly on their morphology, size, surface structure and crystallinity. [17][18][19][20] Therefore, the shape-controlled synthesis and relevant applications of Au NCs have been widely studied and obtained great success during the past decade. Many efforts have been devoted to the shape-controlled synthesis of Au NCs with different morphologies, such as nanospheres, nanorods, nanowires, nanodendrites, nanosheets, nanocombs and pentagon-shaped particles.…”
Section: Introductionmentioning
confidence: 99%
“…3-APTMS capped noble metal cations may be converted into monometallic, bimetallic, and trimetallic nanoparticles in the presence of a small organic reducing agent (e.g., cyclohexanone, tetrahydrofuran hydroperoxide, or formaldehyde) or 3-GPTMS [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. These as-made nanoparticles can be made insensitive to pH changes [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Noble metal nanoparticles with surface functionalization by a organotrialkoxysilane (e.g., 3-aminopropyltrimethoxysilane (3-APTMS) and 3-glycidoxypropylytrimethox ysilane (3-GPTMS)) have potential use in catalytic applications [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. The use of 3-APTMS and 3-GPTMS to synthesize noble metal nanoparticles has previously been demonstrated [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. It has been reported that 3-APTMS capped gold ions are converted into nanoparticles in the presence of reducing agents such as 3-GPTMS, cyclohexanone, tetrahydrofuran hydroperoxide, and formaldehyde.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of AuNPs as a homogenous catalyst involves number of issues, arising from a limited stability thereof, as well as their tendency to aggregate. For these reasons, a special attention should be paid to the approach of AuNPs synthesis [ 21 ].…”
Section: Introductionmentioning
confidence: 99%